2012
DOI: 10.1289/ehp.1104114
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Peripheral Arterial Disease: Results from the NHANES

Abstract: Background: Bisphenol A (BPA) is a common chemical used in the manufacture of polycarbonate plastics and epoxy resins, and > 93% of U.S. adults have detectable levels of urinary BPA. Recent animal studies have suggested that BPA exposure may have a role in several mechanisms involved in the development of cardiovascular disease (CVD), including weight gain, insulin resistance, thyroid dysfunction, endothelial dysfunction, and oxidative stress. However, few human studies have examined the association between ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 28 publications
4
104
2
Order By: Relevance
“…56 A similar association has been reported for organochlorine pesticides. 57 Atherosclerotic PAD is also associated with genetic variants and it is known to have a heritable component.…”
Section: Primary Prevention Of Padsupporting
confidence: 69%
“…56 A similar association has been reported for organochlorine pesticides. 57 Atherosclerotic PAD is also associated with genetic variants and it is known to have a heritable component.…”
Section: Primary Prevention Of Padsupporting
confidence: 69%
“…However, many recent studies have demonstrated observable adverse effects, such as cancer cell proliferation, 36 with BPA doses below the EPA reference dose. [37][38][39] Furthermore, elevated human urinary BPA levels have been associated with peripheral arterial disease, 40 cardiovascular disease, diabetes, abnormal liver enzyme levels, 41 and obesity in children and adolescents. 42 Based on this evidence, it seems prudent to minimize our patients' exposure to BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence has indicated that exposure to BPA is associated with an increased risk of some metabolic diseases such as obesity, insulin resistance, type 2 diabetes, dyslipidemia, etc. (Alonso-Magdalena et al 2011, Shankar et al 2012, Vom Saal et al 2012. The presence of these metabolic disorder events has been documented to predict the future development of NAFLD (Fan et al 2005, Hamaguchi et al 2005.…”
Section: Introductionmentioning
confidence: 99%